Diet analysis of bats killed at wind turbines suggests large‐scale losses of trophic interactions - Carolin Scholz; Christian C. Voigt (Conservation Science and Practice, 2022)
Abstract Agricultural practice has led to landscape simplification and biodiversity decline, yet recently, energy‐producing infrastructures, such as wind turbines, have been added to these simplified agroecosystems, turning them into multi‐functional energy‐agroecosystems. Here, we studied the trophic interactions of bats killed at wind turbines using a DNA metabarcoding approach to shed light on how turbine‐related bat fatalities may possibly affect local habitats. Specifically, we identified insect DNA in the stomachs of common noctule bats (Nyctalus noctula) killed by wind turbines in Germany to infer in which habitats these bats hunted. Common noctule bats consumed a wide variety of insects from different habitats, ranging from aquatic to terrestrial ecosystems (e.g., wetlands, farmland, forests, and grasslands). Agricultural and silvicultural pest insects made up about 20% of insect species consumed by the studied bats. Our study suggests that the potential damage of wind energy production goes beyond the loss of bats and the decline of bat populations. Bat fatalities at wind turbines may lead to the loss of trophic interactions and ecosystem services provided by bats, which may add to the functional simplification and impaired crop production, respectively, in multi‐functional ecosystems.